Cultural markers in MMORPGs:: an analysis of Final Fantasy XIV - Ferreira, Emmanoel (2023)
The objective of this paper is to investigate the presence of cultural markers in roleplay, specifically in MMORPGs, and to discuss them based on the existing literature. We started the research with the textual and paratextual elements that relate to the game, such as in-game elements created by the players – scenarios, clothes, skins – and off-game elements, such as screenshots and comments from players on social networks – in order to analyze the unfolding of their uses, be them intentional or not. Taking as the object of study the Facebook group "Final Fantasy – XIV Brasil", we observe how some of these markers manifest and relate to roleplay, in addition to identifying their influence on social aspects of the group and on the Brazilian community of Final Fantasy XIV players as a whole.